Recrudescent Meibomian Gland Carcinoma Treated with Xeloda: Case Report. Issue 2 (March 2014) - Liang, Yi-chen; Zhang, Tao; Chen, Sheng; Yu, Dan-dan; Wu, Hong-ge
Purpose: To observe the curative effect of Xeloda in meibomian gland carcinoma. Methods: We treated a 53-year-old woman, who had recrudescent meibomian gland carcinoma, with Xeloda. Results: The mass was much smaller with decreased amount of overflow pus after 4 cycles of chemotherapy with Xeloda. Conclusions: Xeloda played a significant role in treating recrudescent meibomian gland carcinoma in this patient.